Amino acid based gallium-68 chelators capable of radiolabeling at neutral pH. Issue 48 (27th November 2017) - Price, Thomas W.; Gallo, Juan; Kubíček, Vojtěch; Böhmová, Zuzana; Prior, Timothy J.; Greenman, John; Hermann, Petr; Stasiuk, Graeme J.
Abstract : Herein we show a flexible synthesis for bifunctional chelators based on amino acids that rapidly complex 68 Ga under physiological conditions. Abstract : Gallium-68 ( 68 Ga) has been the subject of increasing interest for its potential in the production of radiotracers for diagnosis of diseases. In this work we report the complexation of 68 Ga by the amino acid based tripodal chelate H3 Dpaa, and two bifunctional derivatives, H3 Dpaa.dab and H4 Dpaa.ga, under a range of conditions with particular emphasis on the rapid complexation of 68 Ga at pH 7.4. 100 μM H3 Dpaa achieved a radiochemical yield of 95% at pH 7.4 in 5 minutes at 37 °C. The bifunctional derivatives H4 Dpaa.ga and H3 Dpaa.dab achieved 94% and 84% radiochemical yields, respectively, under the same conditions. The resulting Ga(iii ) complexes show thermodynamic stabilities of log  K GaDpaa = 18.53, log  K GaDpaa.dab = 22.08, log  K GaDpaa.ga = 18.36. Unfortunately, the resulting radiolabelled species do not present sufficient serum stability for in vivo application. Herein we show a flexible synthesis for bifunctional chelators based on amino acids that rapidly complex 68 Ga under physiological conditions.